FALLS OF CHILDRENS AND TEENS: PREVENTING INJURIES THROUGH HEALTH EDUCATION - Márcia Adriana Poll; Teresinha Heck Weiller; Rosana Huppes Engel; Tatiane Angélica Phelipini Borges; Andressa Oliveira Rios; Valquiria Acosta Catarina Carpes (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211021 Aim: know the epidemiological profile of children and adolescents affected by falls, looking to help strategies for educational activities in the school to prevent this event in childhood. Method: quantitative research, developed in emergency, with 68 children, in the period of January to June, 2013. The collection was through the records of ambulatory care sheets, analyzed by the Statistic Package for Social Sciences(SPSS®). Results: among 3,144 attendances in emergency, 390 were falls that occurred from zero to nineteen, struck the male. The falls without specifications in the ambulatory sheets were the reason for frequent attendance and the morbidity that most injuries were caused sharps injuries. Conclusions: know the profile of the falls, allows to define priority actions and supporting including prevention, health education and care of victims of these causes.